Formulation Of The Strategy For The Development Of Small Micro Business In The Efforts To Increase The Competitiveness Of Local Agriculture Products (Case Study In Sukoharjo District) - Irma Wardani; Umi Nur Solikah (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2019)
Micro-small scale the agricultural sector in Sukoharjo Regency are the most dominant sector in the community, therefore it is necessary to review micro-small enterprises that are prioritized to be developed. This study aims to damage alternative development strategies in small micro-enterprises in increasing the competitiveness of local products. Data analysis techniques used are AHP, SWOT and QSPM methods The results of the AHP study show that the priorities developed are 1) herbal medicine stalls (0.37124). On the results of the QSP matrix on micro small enterprises, herbal medicine based on the highest score indicates that the product development strategy (5.33). Market development (5.22) and market penetration (5.22). The development strategy is expected to be able to implement product strategies that are in line with market demand with competitive advantages.